COVID-19 government measures and their impact on mental health: a cross-sectional study of older primary care patients in Germany - Wittmann, Felix G.; Zülke, Andrea; Pabst, Alexander; Luppa, Melanie; Thyrian, Jochen René; Kästner, Anika; Hoffmann, Wolfgang; Kaduszkiewicz, Hanna; Döhring, Juliane; Escales, Catharina; Gensichen, Jochen; Zöllinger, Isabel; et al. (Frontiers in Public Health, 2023)
Background: With the outbreak of COVID-19, government measures including social distancing and restrictions of social contacts were imposed to slow the spread of the virus. Since older adults are at increased risk of severe disease, they were particularly affected by these restrictions. These may negatively affect mental health by loneliness and social isolation, which constitute risk factors for depressiveness. We aimed to analyse the impact of perceived restriction due to government measures on depressive symptoms and investigated stress as mediator in an at-risk-population in Germany. Methods: Data were collected in April 2020 from the population of the AgeWell.de-study, including individuals with a Cardiovascular Risk Factors, Aging, and Incidence of Dementia (CAIDE) score ≥ 9, using the depression subscale of the Brief Symptom Inventory (BSI-18) and the Perceived Stress Scale (PSS-4). Feeling restricted due to COVID-19 government measures was surveyed with a standardized questionnaire. Stepwise multivariate regressions using zero-inflated negative binomial models were applied to analyse depressive symptoms, followed by a general structural equation model to assess stress as mediator. Analysis were controlled for sociodemographic factors as well as social support. Results: We analysed data from 810 older adults (mean age=69.9, SD=5). Feeling restricted due to COVID-19 government measures was linked to increased depressiveness (b=0.19; p<0.001). The association was no longer significant when adding stress and covariates (b= 0.04; p=0.43), while stress was linked to increased depressive symptoms (b=0.22; p<0.001). A final model confirms the assumption that the feeling of restriction is mediated by stress (total effect: b=0.26; p<0.001). Conclusion: We found evidence that feeling restricted due to COVID-19 government measures is associated with higher levels of depressive symptoms in older adults at increased risk for dementia. The association is mediated by perceived stress. Furthermore, social support was significantly associated with less depressive symptoms. Thus, it is of high relevance to consider possible adverse effects of government measures related to COVID-19 on mental health of older people.